MIDAS versus mixed-frequency VAR: nowcasting GDP in the euro area - Vladimir N. Kuzin; Massimiliano Marcellino; Christian Schumacher (Deutsche Bundesbank, 2009)
This paper compares the mixed-data sampling (MIDAS) and mixed-frequency VAR (MF-VAR) approaches to model speci…cation in the presence of mixed-frequency data, e.g., monthly and quarterly series. MIDAS leads to parsimonious models based on exponential lag polynomials for the coe cients, whereas MF-VAR does not restrict the dynamics and therefore can suer from the curse of dimensionality. But if the restrictions imposed by MIDAS are too stringent, the MF-VAR can perform better. Hence, it is di cult to rank MIDAS and MF-VAR a priori, and their relative ranking is better evaluated empirically. In this paper, we compare their performance in a relevant case for policy making, i.e., nowcasting and forecasting quarterly GDP growth in the euro area, on a monthly basis and using a set of 20 monthly indicators. It turns out that the two approaches are more complementary than substitutes, since MF-VAR tends to perform better for longer horizons, whereas MIDAS for shorter horizons.
Keywords: C53; E37; 330; nowcasting; mixed-frequency data; mixed-frequency VAR; MIDAS; Konjunkturprognose; Prognoseverfahren; Ökonometrisches Modell; Vergleich; Theorie; Sozialprodukt; EU-Staaten